Curriculum and Learning Management in Implementing the Merdeka Curriculum: A Case Study at MA Mafaza Bantul - Hidayah Nur Fathimah; Priadi Surya (Journal of Educational Sciences, 2026)
This study aims to analyze curriculum and learning management in implementing the Merdeka Curriculum at MA Mafaza Bantul, an Islamic boarding school-based madrasah in Bantul, Yogyakarta. This research employed a descriptive qualitative approach. Data were collected through in-depth interviews with the principal, vice principal for curriculum affairs, teachers, educational staff, and students, supplemented by structured observations and documentation analysis of official curriculum documents including the Madrasah Operational Curriculum. Data validity was ensured through triangulation, while data were analyzed using the interactive model of Miles et al. The findings revealed that curriculum management was implemented through planning, organizing, implementation, and evaluation functions. Curriculum implementation integrated the Merdeka Curriculum, the 2013 Curriculum, and three flagship pesantren programs, namely Tahfidz Al-Qur’an, Science Olympiad, and Qiraatul Khutub. Several challenges were identified, including incomplete teacher administration, limited instructional innovation, and constraints in implementing P5P2RA activities, which were addressed through in-house training, teacher learning communities, and comparative studies. These findings indicate that collaborative leadership, continuous supervision, and adaptive curriculum management are critical factors supporting effective curriculum implementation in pesantren-based madrasahs.